Intermittent Catheters with Integrated Amphiphilic Surfactant Reduce Urethral Microtrauma in an Ex Vivo Model Compared with Polyvinylpyrrolidone-Coated Intermittent Catheters - Luca Barbieri; Makhara S. Ung; Katherine E. Hill; Ased Ali; Laura A. Smith Callahan (Journal of Functional Biomaterials)
Intermittent catheterization mitigates urinary retention for over 300,000 people in the US every year, but can cause microtrauma in the urothelium, compromising its barrier function and increasing the risk of pathogen entry, which may affect user health. To reduce adverse effects, intermittent catheters (ICs) with increased lubricity are used. A common strategy to enhance IC lubricity is to apply a polyvinylpyrrolidone (PVP) coating to ICs; however, this coating can become adhesive upon drying, potentially leading to microtrauma. An alternative approach for lubricity is the migration of integrated amphiphilic surfactant (IAS) within the IC to the surface. The present work examines differences in urethral microtrauma caused by the simulated catheterization of ex vivo porcine urethral tissue using PVP-coated and IAS ICs. Scanning electron microscopy and fluorescence microscopy of the tissue showed the removal of the apical cell layer after contact with the PVP-coated ICs, but not the IAS IC. More extracellular matrices and DNA were observed on the PVP-coated ICs than the IAS IC after tissue contact. Contact angle analysis of the polar and dispersive components of the surface energy demonstrated that the PVP-coated ICs promoted mucoadhesion, while the IAS IC limited mucoadhesion. Overall, the results indicate that IAS ICs cause less microtrauma to urethral tissue than traditional PVP-coated ICs.